Provenance of the lower jurassic quartz-rich conglomerate in northwestern sichuan basin and its link with the pre-collisional unroofing history of the north longmen shan thrust belt, NE tibetan plateau margin - Lv, Fan; Ran, Bo; Liu, Shugen; Wang, Zijian; Sun, Tong; Li, Xianghui; Han, Yuyue; Liang, Ke (Frontiers in Earth Science, 2022)
The research on the pre-collisional tectonic evolution of basin-mountain system at the margin of Tibetan plateau provides insights into the upward and outward growth mechanism of the plateau in the Cenozoic. Lower Jurassic Baitianba Formation quartz-rich conglomerate exposed along the edge of the northwest Sichuan Basin whereas these deposits were incompatible with peripheral carbonatite-dominated orogenic belts, which aroused our great interest. To better understand the origin of quartz-rich conglomerate and early erosional unroofing history of northeastern Tibetan Plateau margin, this study focuses on sandstone petrography analysis along with U-Pb age dating of the detrital zircons of Baitianba Formation gravel and sandstone sample from northwestern Sichuan Basin, which is located to north Longmen Shan thrust belt . In the distinctive Lower Jurassic quartz gravel samples, there are at least two distinct provenance sources. One is characterized by a unimodal age population at ca. 400-1000 Ma but the absence of younger detrital zircons (<395 Ma), resembling the Early Paleozoic marine quartz sandstone due to the uplift and erosion of the Paleozoic basement of the Longmen Shan thrust belt . the other contains zircons of ca. 1.8Ga, 950-750 Ma, 450-420 Ma, 280-240 Ma, which is identical to the detrital zircons from the Upper Triassic. Furtherly, detrital zircon dating of our sandstone samples also exhibit strong similarity to the Upper Triassic strata detrital record. Detrital zircons linked with the sedimentological data show these quartz conglomerate mainly recycled from the underlying Upper Triassic through long-term weathering.